Cellular and Metabolic Basis for the Ichthyotic Phenotype in NIPAL4 (Ichthyin)-Deficient Canines - Mauldin, Elizabeth A; Crumrine, Debra; Casal, Margret L; Jeong, Sekyoo; Opálka, Lukáš; Vavrova, Katerina; Uchida, Yoshikazu; Park, Kyungho; Craiglow, Brittany; Choate, Keith A; Shin, Kyong-Oh; Lee, Yong-Moon; et al. (The American journal of pathology, 2018)
Mutations in several lipid synthetic enzymes that block fatty acid and ceramide production produce autosomal recessive congenital ichthyoses (ARCIs) and associated abnormalities in permeability barrier homeostasis. However, the basis for the phenotype in patients with NIPAL4 (ichthyin) mutations (among the most prevalent ARCIs) remains unknown. Barrier function was abnormal in an index patient and in canines with homozygous NIPAL4 mutations, attributable to extensive membrane stripping, likely from detergent effects of nonesterified free fatty acid. Cytotoxicity compromised not only lamellar body secretion but also formation of the corneocyte lipid envelope (CLE) and attenuation of the cornified envelope (CE), consistent with a previously unrecognized, scaffold function of the CLE. Together, these abnormalities result in failure to form normal lamellar bilayers, accounting for the permeability barrier abnormality and clinical phenotype in NIPA-like domain-containing 4 (NIPAL4) deficiency. Thus, NIPAL4 deficiency represents another lipid synthetic ARCI that converges on the CLE (and CE), compromising their putative scaffold function. However, the clinical phenotype only partially improved after normalization of CLE and CE structure with topical ω-O-acylceramide because of ongoing accumulation of toxic metabolites, further evidence that proximal, cytotoxic metabolites contribute to disease pathogenesis.
Keywords: modely nemocí na zvířatech; fenotyp; Male; Pedigree; homozygot; mutace; ichtyóza; rodokmen; Phenotype; Ichthyosis; Dogs; Adult; dospělí; mužské pohlaví; Homozygote; receptory buněčného povrchu; lipidy; Animals; lidé; ženské pohlaví; Humans; zvířata; Disease Models, Animal; Receptors, Cell Surface; psi; Lipids; Epidermis; Mutation; Female; epidermis